Evidence from a Comprehensive Bioinformatics Analysis Point to Possible Therapeutic Targets for Vitiligo - Wang Y; Yao T; Lin Y; Wu J (Clinical, Cosmetic and Investigational Dermatology)
Yingwei Wang,1,* Tao Yao,2,* Yunlu Lin,2,* Jianming Wu1 1Department of Dermatology, The Second Affiliated Hospital and Yuying Children’s Hospital of Wenzhou Medical University, Wenzhou, Zhejiang, 325000, People’s Republic of China; 2Department of Cardiology, The Second Affiliated Hospital and Yuying Children’s Hospital of Wenzhou Medical University, Wenzhou, Zhejiang, 325000, People’s Republic of China*These authors contributed equally to this workCorrespondence: Jianming Wu, Email wjm9515@163.comBackground: Vitiligo is an autoimmune, hypopigmented dermatological disease for which the pathogenesis remains unclear. With limited therapeutic options, it has a significant treatment burden and adverse psychological effects for patients.Methods: The core method employed was Mendelian randomization (MR), which was used to assess the impact of over 2,000 plasma proteins on generalized vitiligo. To further enhance the reliability of the MR conclusions, we conducted a series of comprehensive analyses, including reverse MR, the Steiger test, colocalization analysis, and phenotype scanning. Subsequently, we employed Phenome-wide MR (PheW-MR) analysis to exclude targets associated with adverse effects and evaluated the druggability of these targets through drug gene list mapping and molecular docking. Additionally, we employed protein-protein interaction (PPI) analysis to elucidate the interactions between the target proteins and existing vitiligo treatments. Finally, pathway enrichment analysis and transcriptome-proteome correlation analysis provided further biological insight into the target proteins.Results: Following a series of comprehensive analyses, we identified three potential drug targets for the treatment of vitiligo: GZMB, FCRL3, and ULK3, each of which is associated with an increased risk of the disease. Validation across different cohorts confirmed the significance of GZMB and FCRL3. Colocalization analysis indicated that these targets share common variants with vitiligo, while PheW-MR analysis suggested that targeting these proteins would not result in significant side effects. Furthermore, molecular docking demonstrated stable binding between the target proteins and predicted drugs. The PPI network revealed that GZMB, FCRL3, and ULK3 interact with the target proteins of existing vitiligo treatments.Conclusion: Our study has identified three promising drug target proteins for the treatment of vitiligo, which merit prioritization in drug development efforts. These targets warrant further investigation to elucidate their underlying mechanisms.Keywords: Mendelian randomization, vitiligo, drug target, protein quantitative trait loci, Bayesian colocalization, molecular docking